2010
DOI: 10.2174/138920010794328913
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Metabolism and Transport in Determining Oral Drug Absorption and Gut Wall Metabolism: A Simulation Assessment Using the “Advanced Dissolution, Absorption, Metabolism (ADAM)” Model

Abstract: Bioavailability of orally administered drugs can be influenced by a number of factors including release from the formulation, dissolution, stability in the gastrointestinal (GI) environment, permeability through the gut wall and first-pass gut wall and hepatic metabolism. Although there are various enzymes in the gut wall which may contribute to gut first pass metabolism, Cytochrome P450 (CYP) 3A has been shown to play a major role. The efflux transporter P-glycoprotein (P-gp; MDR1/ABCB1) is the most extensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
129
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(129 citation statements)
references
References 4 publications
0
129
0
Order By: Relevance
“…The free fraction of drug within the enterocyte is represented by the fu gut term. Detailed description of ADAM model can be found in the publication by Darwich et al [11].…”
Section: Prediction Of Plasma Profiles In Humanmentioning
confidence: 99%
“…The free fraction of drug within the enterocyte is represented by the fu gut term. Detailed description of ADAM model can be found in the publication by Darwich et al [11].…”
Section: Prediction Of Plasma Profiles In Humanmentioning
confidence: 99%
“…There has been some movement in the field to accommodate a reduced or partial intestinal flow to the enterocyte region. The emergence of the Q Gut model (Yang et al, 2007) and the advanced dissolution, absorption, metabolism model from Simcyp (Darwich et al, 2010) favors this concept of partial flow. Other models that further encompass heterogeneity in transporters and enzymes have been adopted to explain the lesser intestinal metabolism observed for drugs given systemically versus orally (Tam et al, 2003;Liu et al, 2006;Bruyère et al, 2010;Gertz et al, 2010) as well as the effect of enterohepatic circulation of glucuronide conjugates (Wu, 2012).…”
mentioning
confidence: 99%
“…The results demonstrated that accounting for the MDR1 distributions enhanced PBPK predictions of bioavailability for the development of the compound under study. Likewise, a study by Darwich and coworkers [56], which incorporated regional MDR1 and CYP3A expression into an ADAM model, demonstrated two points: non-uniform regional distribution of MDR1 in the small intestine and colon, and disparity between mRNA and protein expression. This highlights that protein and mRNA expression together with drug parameter data leads to successful capture of drug disposition.…”
Section: Intestinal Transporters Linked To Ivive-pbpk Model For Oral mentioning
confidence: 97%
“…Advanced models such as the advanced dissolution, absorption, and metabolism (ADAM) model and the advanced compartmental absorption and transit model (ACAT) are based on adaptations of the original compartmental absorption and transit (CAT) model which accounts for small intestinal transit time (SI), permeability, and radii. Most importantly, these advanced models incorporate gastrointestinal transporter-metabolism interplay [55,56]. A study by Bruyere and co-workers has highlighted the importance of obtaining regional intestinal transporter expression data for incorporation in PBPK models [57].…”
Section: Intestinal Transporters Linked To Ivive-pbpk Model For Oral mentioning
confidence: 99%